Contact mechanics and friction : physical principles and applications - Popov, Valentin L. (Springer, 2017)
This text introduces the associations between contact mechanics and friction, offering a deep understanding of tribology. It deals with the associated phenomena of contact, adhesion, capillary forces, friction, lubrication, and wear from a single viewpoint.